The oral health status and knowledge of the elementary students of agape international ministries (AIM) Christian Learning Center, Sampaloc, Manila - Bautista, Kamille Joanna B.
Dental caries has been named as one of the common oral diseases which is a significant problem in public health. Oral health program promotes dental health activities designed to encourage good dental health practices, help prevent dental caries and other oral diseases. This descriptive study aimed to determine the oral health knowledge and status of the elementary students of AIM Christian Learning Center located in Sampaloc, Manila and to develop an oral health program appropriate for the school. Seventy-five elementary students were asked to participate in the study. 66 students took the knowledge test and 70 students in the oral examination. Oral health knowledge test, oral examination to determine caries prevalence, DMFT/dft, OHI-scores, and interview regarding oral hygiene practices were conducted. Results showed that caries prevalence of the participants were consistent with the NMEDS standard (94.4% for the temporary teeth and above 90% for the permanent teeth). Caries prevalence of Grade V showed lower score (66.67%) compared with the standard. Mean dft score of the students (5.84) is higher than the NMEDS standard (4.56 mean DMFT for 12 y/o), while mean DMFT score (4.37) is lower. 91% passed the oral health knowledge test among grades I-II while 48% passed among Grades III-VI; passing rate was 80%, 5% higher than the school's grading system, 75%. All grade levels showed OHI scores ranging 0.17 - 1.51, which was considered as falling into the "good" oral hygiene practice. 100% claimed to use toothbrush with toothpaste as tooth cleaners. 4.29% of them said that other tooth cleaners aside from toothbrushes were being used such as floss, mouthwash and orthobrush. Majority of the students brush their teeth twice a day. Majority of them need restoration or extraction of decayed teeth. The oral health status of the elementary students of AIM Christian Learning Center showed showed caries prevalence consistent with the NMEDS standard which is 94.4% for the temporary teeth and above 90% for the permanent teeth, DMFT score (4.37) and mean dft scores (5.84) and OHI-scores ranging from 0.17-1.51 which indicate "good" oral hygiene practice. 91% among Grades I-II, and 48% among Grades III-VI are knowledgeable on oral health.